2012
DOI: 10.1111/j.1365-2826.2012.02299.x
|View full text |Cite
|
Sign up to set email alerts
|

P2X Purinergic Receptor Knockout Mice Reveal Endogenous ATP Modulation of Both Vasopressin and Oxytocin Release from the Intact Neurohypophysis

Abstract: Bursts of action potentials are crucial for neuropeptide release from the Hypothalamic Neurohypophysial System (HNS). The biophysical properties of the ion channels involved in release of these neuropeptides cannot explain the efficacy of such bursting patterns on secretion. We have previously shown that ATP, acting via P2X receptors, potentiates only AVP release from HNS terminals, whereas, its metabolite adenosine, via A1 receptors acting on transient Ca2+ currents, inhibits both AVP and OT secretion. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In a later study, it was suggested that co-released ATP potentiates vasopressin release through the activation of P2X2Rs, P2X3Rs, P2X4Rs, and P2X7Rs whereas oxytocin release is mediated only through the P2X7R [100]. Using electrical stimulation of isolated and intact mouse posterior pituitaries, the concept was supported that the co-released endogenous ATP acts as a paracrineautocrine messenger, enhancing vasopressin secretion from neurohypophysial nerve terminals [104].…”
Section: Neuropeptides From the Hypothalamo-posterior Pituitary Unitmentioning
confidence: 86%
See 1 more Smart Citation
“…In a later study, it was suggested that co-released ATP potentiates vasopressin release through the activation of P2X2Rs, P2X3Rs, P2X4Rs, and P2X7Rs whereas oxytocin release is mediated only through the P2X7R [100]. Using electrical stimulation of isolated and intact mouse posterior pituitaries, the concept was supported that the co-released endogenous ATP acts as a paracrineautocrine messenger, enhancing vasopressin secretion from neurohypophysial nerve terminals [104].…”
Section: Neuropeptides From the Hypothalamo-posterior Pituitary Unitmentioning
confidence: 86%
“…Examples include noradrenaline [80] or glutamate [49,50]. Additional examples for enhanced messenger release by autocrine action of ATP include the release of vasopressin [104], gonadotrophins [109,110], prolactin [114], IL-1β [291], IL-6 [353], CXCL8 [142], IL-10, or IL-33 [311]. Signal maintenance or amplification by ATP-induced ATP release may thus be of considerably greater physiological relevance than hitherto anticipated.…”
Section: Atp-mediated Atp Releasementioning
confidence: 99%
“…4). Interestingly, such autocrine positive feedback has also been described for synaptic ATP release in the carotid body [67] and at terminals of neurosecretory cells in the posterior pituitary [68]. Thus, what was initially interpreted as being strictly a postsynaptic deficit of sensory fibers (absence of postsynaptic receptors in the P2X2/P2X3 knockout mice), is now understood to include a profound deficit in presynaptic release mechanisms in taste bud cells.…”
Section: Cell–cell Communication and Taste Receptionmentioning
confidence: 97%
“…Electrophysiological evidence for the existence of P2XR currents in vasopressinergic PP terminals but not in terminals labeled for oxytocin have also been shown . Experiments with knockout mice revealed that sufficient endogenous ATP is released by bursts of action potential to act at P2X2Rs, but not at P2X3R or P2X7R …”
Section: Hypothalamo‐posterior Pituitary Systemmentioning
confidence: 98%